Speckle tracking imaging evaluation of left ventricular myocardial work comparing right ventricular septal pacing with His-Purkinje system area pacing - Meng, Qingguo; Li, Yao; Wang, Sijia; Feng, Tianhang; Xu, Huijun; Liu, Juan; Liu, Xuebing; Guo, Zhiyu; Deng, Yan; Li, Chunmei; Tang, Yijia; Yin, Lixue (Frontiers in Cardiovascular Medicine, 2022)
Aims We sought to objectively assess left ventricular myocardial work (MW) parameters after right ventricular septal pacing (VSP) and His-Purkinje system area pacing (HPSAP) procedures. Methods Patients undergoing double-chamber pacemaker implantation for III-degree atrioventricular block (III° AVB) were assessed one year after implantation. VSP and HPSAP groups (20 and 23 patients, respectively) were compared against 40 healthy age-matched volunteers. Two-dimensional ultrasound speckle tracking imaging was used to obtain global myocardial work index (GWI), global myocardial work efficiency (GWE) and global myocardial constructive work (GCW), global myocardial wasted work (GWW), left ventricular stratified strain and peak strain dispersion (PSD). Results GWI, GWE and GCW parameters were improved in HPSAP compared to the VSP while GWW was significantly larger in the VSP group compared to the HPSAP group (all p<0.05). HPSAP outperformed the VSP group in comparisons of global left ventricular longitudinal strain and stratified strain. Compared to controls, the GCW of all segmental myocardium (17/17 segments) in the VSP group was significantly reduced, while 70.59% (12/17 segments) in the HPSAP group were lower than the control group. GCW in the left ventricular segment of the HPSAP group was bigger than VSP group (29.41%; 5/17 segments), and mainly concentrated in the ventricular septum and inferior wall. Conclusions Our findings suggest that HPSAP performance outcomes are improved over VSP after one year, especially in left ventricular contractile synchrony, and HPSAP is beneficial to the effective myocardial work of the left ventricle.